KANDUNGAN MIKROFOSIL DALAM FORMASI PEMBAWA BATUBARA DARI DAERAH PERIAN KECAMATAN MUARA MUNTAI, KABUPATEN KUTAI KERTANEGARA, KALIMANTAN TIMUR - -, Winantris; -, Ildrem Syafri; -, Rusman Rinawan (Bulletin of Scientific Contribution, 2006)
The research uses two kinds of microfossils for an aim to produce more precision, which Palinomorph as a main object and foraminifera as the support object. Pollen analysis has the main role in paleo-environment reconstruction, based on ecological characteristics plants association. Using palinomorph and foraminifera together in one research can only be conducted through sediments transition. Coals are included in the category, where coal samples were taken from Sungai Perian near Pulaubalang-Pamaluan formation boundary.From four samples that were analyzed (1R / claystone, 3R / claystone, 5R / claystone carbonaceous, and 7R / claystone) 53 genera and only 5 foraminifera species was founded. Both microfossils have yielded the same interpretation. The relative ages of the pollen indicator are from Middle-Early Miocene, and the relative ages of the foraminifera are from Late-Early Miocene. Based on the palinomorph and foraminifera data the research area was on regressions environment during the geologic period mentioned.